Integrated systems simulation for assessing fuel thermal management capabilities for hybrid-electric rotorcraft - Roumeliotis, Ioannis; Castro, Lorenzo; Jafari, Soheil; Pachidis, Vassilios; De Riberolles, Louis; Broca, Olivier; Unlu, Deniz (American Society of Mechanical Engineers (ASME), 2021)
Future aircraft and rotorcraft propulsion systems should be able to meet ambitious targets and severe limitations set by governments and organizations. These targets cannot be achieved through marginal improvements in turbine technology or vehicle design. Hybrid-electric propulsion is being widely considered as a revolutionary concept to further improve the environmental impact of air travel. One of the most important challenges and barriers in the development phase of hybrid-electric propulsion systems is the Thermal Management System (TMS) design, sizing and optimization for addressing the increased thermal loads due to the electric power train. The aim of this paper is to establish an integrated simulation framework including the vehicle, the propulsion system and the fuel-oil system (FOS) for assessing the cooling capability of the FOS for the more electric era of rotorcrafts. The framework consists of a helicopter model, propulsion system models, both conventional and hybrid-electric, and a FOS model. The test case is a twin-engine medium (TEM) helicopter flying a representative Passenger Air Transport (PAT) mission. The conventional power plant heat loads are calculated and the cooling capacity of the FOS is quantified for different operating conditions. Having established the baseline, three different Power Management Strategies (PMS) are considered and the integrated simulation framework is utilized for evaluating FOS temperatures. The results highlight the limitations of existing rotorcraft FOS to cope with the high values of thermal loads associated with hybridization for the cases examined. Hence, new ideas and embodiments should be identified and assessed. The case of exploiting the fuel tank as a heat sink is investigated and the results indicate that recirculating fuel to the fuel tank can enhance the cooling capacity of conventional FOS.